Searching for Japan : twentieth-century Italy's fascination with Japanese culture - Monserrati, Michele, 1977- (Liverpool : Liverpool University Press, 2020)
This book pursues the specific case of Italian travel narratives in the Far East, through a focus on the experience of Japan in works by writers who visited the Land of the Rising Sun beginning in the Meiji period (1868-1912) and during the concomitant opening of Japan's relations with the West.
Cover -- Contents -- List of Illustrations -- Acknowledgements -- Introduction: Searching for Japan -- 1. Cosmopolitan Possibilities in Translation: Views from the Russo-Japanese War -- 2. Mussolini in Japan: Japanese Representations in the Age of Fascism -- 3. Little Italy, Big Japan: Patterns of Continuity and Displacement among Italian Writers in Japan -- 4. Madama Butterfly Revised -- Postscript -- Index
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on September 23, 2020).
JSTOR
Keywords: Travelers' writings, Italian -- History and criticism; Japan -- Description and travel; Italy -- Civilization -- Japanese influences; Japan -- Civilization -- Italian influences; Japon -- Descriptions et voyages; LITERARY CRITICISM -- European -- Italian; Civilization -- Japanese influences; Civilization -- Italian influences; Travel; Travelers' writings, Italian; Italy; Japan; Criticism, interpretation, etc